HUBUNGAN PERSEPSI PEGAWAI TENTANG KEPEMIMPINAN PERAWAT SEBAGAI KEPALA PUSKESMAS TERHADAP KINERJA - Gulo, Cipta (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Leadership plays an important role in achieving organization’s success. Efforts to improve the performance of health workers require the role of a puskesmas head in taking an effective leadership approach. Individual perception of leadership brings impacts on their performances. The objective of the research was to discover and analyze the correlation between employees’ perception of nurse’s leadership as the Head of Puskesmas and their performances at Puskesmas in Nias Barat Regency. This is a quantitative research. It employed Spearman‘s correlation research design. The population covered all employees in the Puskesmas in Nias Barat Regency who are led by a nurse. There were 5 Puskesmas led by a nurse; so the population was 160 nurses who were all taken as the research samples by applying total sampling technique. The data were analyzed using univariate and bivariate analysis. Bivariate analysis using Spearman’s correlation test to test the correlation between employees’ perception of nurse’s leadership as the head of Puskesmas and the employees’ performances at Puskesmas in Nias Barat Regency was p score 0.000 < 0.05. It concluded that there was a significant correlation between both variables, with r 0.775 indicating that the correlation strength was categorized into strong correlation. It is suggested, based on the research results, that the nurse as head of puskesmas take part in trainings relevant to management of puskesmas in order to increase their knowledge and experience of leadership in puskesmas and continue giving positive motivation to the employees; as well as support the career development of the employees in order to improve their performances.